2008
DOI: 10.1002/ijc.23573
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain pathogenicity of MSH2 variants N127S and G322D challenges their classification

Abstract: Hereditary non-polyposis colorectal cancer (HNPCC) is associated with germline mutations in mismatch repair (MMR) genes. Inherited missense mutations, however, complicate the diagnostics because they do not always cause unambiguous predisposition to cancer. This leads to variable and contradictory interpretations of their pathogenicity. Here, we establish evidence for the functionality of the 2 frequently reported variations, MSH2 N127S and G322D, which have been described both as pathogenic and nonpathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Moreover, p.Gly322 is a conserved amino acid suggesting its importance. Irrespective of the recent study, where enhancer screens with the yeast homolog msh2 p.Gly317Asp did not yield enhancer mutations [Martinez and Kolodner, 2010] and our previous study, where the purified p.Gly322Asp variant did not show MMR deficiency [Ollila et al, 2008], here the total protein extract with over expressed MSH2 p.Gly322Asp individually and as a pair with p.Asp487Glu show a statistically significant decrease in repair efficiency. It is possible that the purification process has at least partly excluded structurally damaged heterodimers suggesting that the in vitro MMR assay performed with total extract is more reliable.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, p.Gly322 is a conserved amino acid suggesting its importance. Irrespective of the recent study, where enhancer screens with the yeast homolog msh2 p.Gly317Asp did not yield enhancer mutations [Martinez and Kolodner, 2010] and our previous study, where the purified p.Gly322Asp variant did not show MMR deficiency [Ollila et al, 2008], here the total protein extract with over expressed MSH2 p.Gly322Asp individually and as a pair with p.Asp487Glu show a statistically significant decrease in repair efficiency. It is possible that the purification process has at least partly excluded structurally damaged heterodimers suggesting that the in vitro MMR assay performed with total extract is more reliable.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, of the eight analyzed VUS pairs, MSH2 p.Asn127Ser/p.Ala328Pro and MSH2 p.Gly322Asp/p.Asp487Glu show significantly decreased repair efficiency. In both pairs, one of the partners is a rare variation, whereas the other (p.Asn127Ser and p.Gly322Asp) is among the most frequently reported VUS in CRC [Hampel et al, 2006; Ollila et al, 2008]. Of these pairs, especially p.Asn127Ser/p.Ala328Pro suggests a concomitant contribution to the MMR deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining VUS for both genes were selected in an unbiased fashion and were predominantly derived from Dutch and Danish suspected LS patients. [Kolodner et al, 1999], 9 [Berends et al, 2002], 10 [Niessen et al, 2006], 11 [Woods et al, 2005], 12 [Belvederesi et al, 2008], 13 [Mastrocola and Heinen, 2010], 14 [Ollila et al, 2008], 15 [Wielders et al, 2011], 16 [Ollila et al, 2008], 17 [Guerrette et al, 1998], 18 [Yang et al, 2004]. d MAPP-MMR [Chao et al, 2008] All MSH2 and MSH6 VUS proteins were generated by the twostage PCR procedure, followed by their expression in vitro.…”
Section: Mmr Activities Of Msh2 and Msh6 Vusmentioning
confidence: 99%
“…We and other groups have addressed this challenge by studying the phenotypic consequences of nontruncating patient-derived MMR gene mutations in functional assays [Kariola et al, 2002[Kariola et al, , 2004Ollila et al, 2006b;Ou et al, 2007;Raevaara et al, 2005]. In our previous MSH2 studies, including 17 nontruncating MSH2 variants found in putative HNPCC patients [Ollila et al, 2006b[Ollila et al, , 2008, we showed that 12 of them impaired MMR. These could therefore be clearly classified as predisposing to HNPCC.…”
Section: Introductionmentioning
confidence: 96%